2020
DOI: 10.1152/ajprenal.00264.2020
|View full text |Cite
|
Sign up to set email alerts
|

A role for tubular Na+/H+exchanger NHE3 in the natriuretic effect of the SGLT2 inhibitor empagliflozin

Abstract: Inhibitors of the proximal tubular sodium glucose cotransporter SGLT2 are natriuretic and they lower blood pressure. There are reports that the activities of SGLT2 and the Na+-H+-exchanger, NHE3, are coordinated. If so, then part of the natriuretic response to an SGLT2 inhibitor is mediated by suppressing NHE3. To examine this further, we compared the effects of the SGLT2 inhibitor, empagliflozin, on urine composition and systolic blood pressure (SBP) in non-diabetic mice with tubule-specific NHE3 knock-down (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(119 citation statements)
references
References 74 publications
5
113
0
1
Order By: Relevance
“…Studies in mice have shown a functional relationship between SGLT2 and NHE3 (Onishi et al, 2019). In non-diabetic mice, SGLT2 inhibition with empagliflozin inhibited NHE3 activity and decreased urinary pH and bicarbonate excretion (Figure 1) (Onishi et al, 2020). Notably, chronic empagliflozin treatment in Akita mice increased a-ketoglutarate, which may drive distal sodium chloride reabsorption to compensate for the decreased proximal sodium reabsorption.…”
Section: Blood Pressure Effectsmentioning
confidence: 96%
“…Studies in mice have shown a functional relationship between SGLT2 and NHE3 (Onishi et al, 2019). In non-diabetic mice, SGLT2 inhibition with empagliflozin inhibited NHE3 activity and decreased urinary pH and bicarbonate excretion (Figure 1) (Onishi et al, 2020). Notably, chronic empagliflozin treatment in Akita mice increased a-ketoglutarate, which may drive distal sodium chloride reabsorption to compensate for the decreased proximal sodium reabsorption.…”
Section: Blood Pressure Effectsmentioning
confidence: 96%
“…Moreover, NaCl delivery to the distal nephron reduces the glomerular filtration rate (GFR) by increasing hydrostatic pressure in Bowman’s space [ 6 ]. Natriuresis may further be promoted through the suppression of sodium–hydrogen exchanger (NHE3) activity, usually upregulated in diabetes [ 8 ].…”
Section: Mechanisms Of Renal Protection With Sglt2mentioning
confidence: 99%
“…Although we previously reported that inhibition of glucose uptake by SGLT2 siRNA or removal of glucose from medium is sufficient to induce cell phenotypic changes, such as suppression of cell senescence [ 14 ] or an increase in angiogenic factor secretion [ 7 ], the intracellular glucose level must be taken as the sum of glucose taken up from extracellular spaces and that generated intracellularly. SGLT2 inhibitors reportedly increase expression of genes involved in gluconeogenesis [ 15 , 16 ]. An increase in intracellular glucose production via de novo pathways may attenuate the concentration gradient of glucose between the cytosol and interstitium, thereby counteracting glucose influx through GLUT2.…”
Section: Discussionmentioning
confidence: 99%